Alternate Fractionation in Radiotherapy Paradigm Change (Radiation Oncology, 2018)
This book, written by leading international experts, describes alternate fractionation strategies in which technology-driven precise targeting and dosing allow for improved conformance and decreased volumes, with concordant lessening of toxicity, reduction in treatment time, and lower overall health care expense. The aim is to provide the advanced clinician with an up-to-date evidence-based reference that will assist in the delivery of enhanced patient care in daily practice. Traditional multi-week fractionation schedules were established at a time when the inclusion of relatively large amounts of normal tissue was unavoidable owing to the lack of accurate target localization during treatment. Such schedules are time and resource consuming, difficult for patients, and expensive. Nevertheless, acceptance of alternate fractionation strategies has been slow in some countries. The paradigm is, however, changing as evidence accumulates to demonstrate improved local control, equivalence of tolerance, or both. In documenting these alternate strategies, this book will be of value for radiation oncologists, medical physicists, and oncologists worldwide.